Pengaruh Variasi Minuman Serbuk Kombinasi Daun Binahong (Anredera Cordifolia (Ten) Steenis) dan Daun Mint (Mentha Piperita L.) terhadap Radikal DPPH (1,1-diphenyl-2-picrylhydraz) - Ni Putu Laras Ayu Ningrat; Wintariani Wintariani; Ngurah Mayun (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Air pollution has become a serious issue, prompting considerations on obtaining essential substances known as antioxidants for the body. Preventive measures can be taken by utilizing herbal plants such as binahong and mint, known for their antioxidant properties.Objective: Measure the activity of the radical barrier of DPPH powder drink. Method: This study was a genuine research type. Results: Phytochemical screening revealed the presence of alkaloids, tannins, and saponins in the positive samples. The inhibition activity results for single formulations were as follows: binahong formulation 83,835%, mint formulation 85,011%, formulation (1 : 1) 83,043%, formulation (1 : 2) 83,210%, and formulation (2 : 1) 81,259%. Organoleptic tests indicated that formulation III was acceptable based on sensory evaluation. Conclusion: The powdered drink combination of binahong and mint leaves contains antioxidant compounds: alkaloids, flavonoids, tannins, and saponins. The highest DPPH radical scavenging activity was observed in the single mint leaf formulation and the lowest barrier is in combination powder drinks with (1 : 1) formulation, and formulation (1:1) was most acceptable based on sensory evaluation and there is no influence of variation between powdered drink formulation series..